UNLOCKING CLUES THROUGH DENTAL RECORDS: A DESCRIPTIVE ANALYSIS OF DENTISTS’ ROLE IN FORENSIC INVESTIGATIONS - Zaheen, Uzma; Khan, Haroon Anwar (Pakistan Journal of Physiology, 2024)
Background: Dental records have become a crucial source of information to forensic odontology’s impressive expansion, particularly in medicolegal instances. Dentists are required by law to maintain patient records. Dental remains typically last longer in fatal conditions, assisting with personal identification in mass tragedies, law enforcement investigations, and medicolegal matters. It is mandated by law that every dentist must keep some kind of records for every patient they treat; demands of busy clinics often result in neglect of this obligation. The purpose of this study was to assess dentists’ knowledge regarding dental record maintenance. Methods: It was a cross-sectional observational study. Data was collected using a questionnaire administered through personal interviews. The purpose of the questionnaire was to gauge the dentists’ understanding of forensic odontology techniques as well as their routine practices for keeping dental records. The gathered data underwent descriptive analysis before being condensed and analysed with SPSS-20. Results: Only a very small percentage (22%) of the dentists maintained records on a regular basis, while majority (78%) did not maintain any records. Conclusion: Only a minority of dentists in Lahore retain dental records, indicating poor record-keeping methods. This causes lack of forensic utilization of valuable and reliable information in medicolegal issues. Pak J Physiol 2024;20(2):61-4,